Sillaginid fishes of Palk Bay and Gulf of Mannar with an account on the maturation and spawning of Indian sand whiting, Sillago sihama (Forsskal)* - Jayasankar, P (Indian Journal of Fisheries, 2011)
In the Palk Bay and Gulf of Mannar 6 species of the family Sillaginidae occurred: Sillago (Sit. faginopodys) chondropus. Silfago (Silfago) sihama. Sil/ago (Sil/ago) indica, Sil/ago (Parasillago) vinÂ· centi, Sillago (Parasillago) argentifasciata and Silfago (ParasiUago) soringa, A key to the idenLificaLion of these species is given and their morphometric and meristic characters tabulated. S. ihama, the mOSL dominant sillaginid species in this region, was a prolonged breeder. The spawning season of Lhis species extended from July to February, with peak spawning activity durinll July to November. Lengths aL first maturity of females and males were 179 and 159 mm respectively. Fecundity varied from 6956 to 48373 and showed. high correlation with length, body weight and ovary weight of the fish, Overall sex ratio indicated predominance of females. Length-related sex ratio showed significant dominance of males tin 170 mm and that of females above this length.